Celebrity fan-engagement on Instagram and how it influences perceptions on hijab culture among young Muslim women in Malaysia - Tengku Mohd Azzman, Tengku Siti Aisha; A. Manaf, Aini Maznina (2018)
Instagram is one of the most popular social networking sites used to follow celebrities and public figures, particularly among female users. Celebrities who use Instagram can influence their female followers in many ways, for instance in influencing their perceptions on body image, adoption of healthy eating lifestyles, and purchase of products or services endorsed by these celebrities.